Implementation of the Realistic Mathematics Education (RME) Approach in Geometry Learning in Secondary Schools - Nur Hakim; Apriyanto Apriyanto; Mardiati Mardiati; Ediaman Sitepu (PT. Anagata Sembagi Education, 2024)
This study aims to analyze the implementation of the Realistic Mathematics Education (RME) approach in geometry learning in secondary schools. Realistic Mathematics Education, which emphasizes mathematics learning through relevant contexts and students' real experiences, aims to improve students' understanding and skills in geometry. This study evaluates the effectiveness of the implementation of RME and identifies various challenges and potential solutions in its implementation. The method used is a literature review that includes studies related to the implementation of RME in geometry learning. The results of the analysis show that RME can improve students' understanding of geometric concepts by linking materials to everyday situations, thereby motivating and involving students more actively in the learning process. This approach helps students link theory to real practice, deepen their understanding, and develop problem-solving skills. There are challenges such as teacher readiness, limited resources, and limited time allocation, recommendations to improve teacher training, develop supportive policies, and provide adequate resources can help overcome these problems. With the right strategy and adequate support, RME has great potential to improve the quality of geometry learning in secondary schools and have a positive impact on student learning outcomes